2016
DOI: 10.1093/bioinformatics/btw194
|View full text |Cite
|
Sign up to set email alerts
|

MINTbase: a framework for the interactive exploration of mitochondrial and nuclear tRNA fragments

Abstract: Motivation: It has been known that mature transfer RNAs (tRNAs) that are encoded in the nuclear genome give rise to short molecules, collectively known as tRNA fragments or tRFs. Recently, we reported that, in healthy individuals and in patients, tRFs are constitutive, arise from mitochondrial as well as from nuclear tRNAs, and have composition and abundances that depend on a person’s sex, population origin and race as well as on tissue, disease and disease subtype. Our findings as well as similar work by othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 29 publications
4
95
0
Order By: Relevance
“…The proper identification of isomiRs between studies is still an open problem, since different tools and research groups utilize different nomenclatures and representations. To this end, we adopted a unique identifier (UID), or 'IsomiR license plate', inspired by the MINTmap approach for tRNA fragments [52,53] and acting as a sequence-dependent unique ID that is independent of genome assembly and doesn't require a brokering naming mechanism. Any isomiR sequence can be mapped to a UID and any UID can be converted back to the isomiR sequence it represents ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The proper identification of isomiRs between studies is still an open problem, since different tools and research groups utilize different nomenclatures and representations. To this end, we adopted a unique identifier (UID), or 'IsomiR license plate', inspired by the MINTmap approach for tRNA fragments [52,53] and acting as a sequence-dependent unique ID that is independent of genome assembly and doesn't require a brokering naming mechanism. Any isomiR sequence can be mapped to a UID and any UID can be converted back to the isomiR sequence it represents ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Sixth, the identity(ies) of the signal(s) from mitochondria responsible for changes in DNA methylation and gene expression have not yet been determined. In addition to metabolite differences discussed above, ncRNA, tRNA and tRF, which were once disregarded as useless fragments of RNA, are now increasingly recognized as important (5961). tRNA represent about 4%–10% of the total cellular DNA; yet, are the predominate transcripts encoded by mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…tRNA represent about 4%–10% of the total cellular DNA; yet, are the predominate transcripts encoded by mtDNA. It has been shown that tRF can affect gene silencing (5961). …”
Section: Discussionmentioning
confidence: 99%
“…The lookup table is then used to process a (quality-filtered and adaptertrimmed) short RNA-seq dataset to generate a tRF expression profile table. For each tRF, MINTmap identified whether it is exclusive to tRNA space [37,38]. Because tRF-1s are derived from the precursor tRNAs, they require a different type of analytical work than fragments that overlap with the mature tRNA, and as such, tRF-1s were not included in our data.…”
Section: Rna Sequence Processing and Expression Analysismentioning
confidence: 99%